A computational modeling study on the helium atmospheric pressure plasma needle discharge - 钱沐杨 杨从影 刘三秋 王震东 吕燕 王德真 (Chinese physics B, 2015)
A two-dimensional coupled model of neutral gas flow and plasma dynamics is employed to investigate the streamer dynamics in a helium plasma needle at atmospheric pressure. A parametric study of the streamer propagation as a function of needle tip curvature radius and helium gas flow rate is presented. The key chemical reactions at the He/air mixing layer which drive the streamer propagation are the direct ionization via collision with electrons, the Penning effect being not so crucial. With increasing the gas flow rate from 0.2 standard liter per minute（SLM） to 0.8 SLM, however, the emissions resulting from reactive oxygen and nitrogen species change from a solid circle to a hollow profile and the average streamer propagation velocity decreases. Air impurities（backdiffusion from ambient air） in the helium jet result in a significant increase in the streamer propagation velocity. Besides, with decreasing the tip curvature radiusfrom 200 μm to 100 μm,the electron avalanche process around the near-tip region is more pronounced. However, the spatially resolved plasma parameters distributions（electron, helium metastables, ground state atomic oxygen, etc.） remain almost the same, except that around the near-tip region where their peak values are more than doubled.